Altered gray matter volume in sensorimotor and thalamic regions associated with pain in localized provoked vulvodynia: a voxel-based morphometry study. Issue 7 (July 2019) - Bhatt, Ravi R.; Gupta, Arpana; Rapkin, Andrea; Kilpatrick, Lisa A.; Hamadani, Kareem; Pazmany, Els; Van Oudenhove, Lukas; Stains, Jean; Aerts, Leen; Enzlin, Paul; Tillisch, Kirsten; Mayer, Emeran A.; et al.
Abstract : Abstract: Multimodal neuroimaging studies provide support for a role of alterations in sensory processing circuits and endogenous pain modulatory systems in provoked vestibulodynia (PVD). In this study, we tested the hypotheses that PVD compared with healthy controls (HCs) would demonstrate gray matter volume (GMV) alterations in regions associated with sensorimotor, corticothalamic, and basal ganglia circuits. We also tested the replicability of previously reported gray matter increases in basal ganglia and hippocampal volumes in PVD vs HCs. In addition, disease specificity of GMV alterations were examined by comparing PVD with another chronic pain disorder. Finally, we examine whether GMV alterations are correlated with symptom measures. Structural magnetic resonance imaging was obtained in 119 premenopausal women (45 PVD, 45 HCs, and 29 irritable bowel syndrome [IBS]). A voxel-based morphometry analysis was applied to determine group differences in the hypothesized regions of interest. Compared with HCs, PVD women exhibited greater GMV in the basal ganglia, hippocampus, and sensorimotor cortices. Compared to patients with IBS, women with PVD had greater GMV in the hippocampus, and sensorimotor network, but lower GMV in the thalamus and precentral gyrus. Regional GMV alterations were associated with patient reports of pain during intercourse and muscle tenderness. The current findings provide further evidence that GMV is increased in PVD compared with HCs in several regions of the sensorimotor network and the hippocampus in patients with PVD. In addition, GMV distinct alterations in the sensorimotor network were identified between 2 pelvic pain disorders, PVD compared with IBS. Abstract : Women with provoked vestibulodynia show gray matter alterations in regions responsible for sensorimotor/pain processing, which are associated with pain during intercourse and muscle tenderness.